THE EFFECT OF APPLICATION OF INQUIRY TRAINING LEARNING MODEL ON SKILL AND PHYSICAL LEARNING OUTCOMES OF STUDENTS - Panto Lumbanraja; Karya Sinulingga; Sumitta Sitanggang (Jurnal Pendidikan Fisika, 2017)
Abstract. This study aims to determine the effect of learning model inquiry training on student learning outcomes on the subject matter of Gas Kinetic Theory. This type of research is quasi experiment. The population in the study were all students of class XI IPA SMAN 7 Medan consisting of 7 classes. Sampling is done by cluster random sampling by taking 2 classes from 7 classes randomly that is class XI-IPA 4 as experiment class and class XI-IPA 3 as control class. Instruments used in peneliatian is essay test with number of problem 8 pieces, attitude observation sheet and skill assessment sheet. The data in this research is analyzed by hypothesis test. The result of this research is the average value of pretest of experiment class 32,50 and control class 31,58. The mean value of the experimental class postes is 78.44 and the control class is 68.16. Based on the result of t test analysis, there is influence of learning inquiry training model to the students' learning result on the subject of kinetic theory of gas class XI SMA Negeri 7 Medan.